Creating Conditions for Promising Collaboration Alliances, Networks, Chains, Strategic Partnerships - Kaats, Edwin; Opheij, Wilfrid; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This publication focuses on the conditions for promising collaboration. Collaboration is becoming a dominant instrument in today's economy and society and manifests itself in many shapes and forms. It is a challenging instrument which still isn't very well understood and poses the business community in front of a number of challenging dilemma's. We position collaboration as a multidisciplinary phenomenon and - based on years of research and as reflective practitioners - offer a comprehensive model for analyzing and designing collaborative processes that is both scientifically rooted and applicable in practice. A better understanding of collaborative processes will enhance the success of alliances, networks, chains and strategic partnerships. In addition to this we look to the future of organizing from a collaborative perspective and address the challenges ahead.
Introduction -- Collaboration: A Fundamental Capability in Society and Organization -- Essential Conditions for Promising Collaboration -- Future Perspectives on Collaboration.
Keywords: Economics; Industrial organization (Economic theory).; Applied psychology; Economics/Management Science; Business Strategy/Leadership.; Organizational Studies, Economic Sociology; Industrial, Organisational and Economic Psychology; Industrial Organization